دور الأقسام الخاصة في تعزيز الخصائص النمائية لدى الطفل المصاب بالتوحد - دراسة مقارنة - - بيزات, عمرية; جعلاب, محمد الصالح (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة إلى التعرف على أثر البرنامج التربوي وعملية الإدماج في الأقسام الخاصة في تطوير وتعزيز الخصائص النمائية لدى الأطفال المصابين بالتوحد، حيث اخترنا عينة تكونت من 10 أطفال منهم خمس حالات للأطفال المصابين بالتوحد مدمجين بالأقسام الخاصة وخمس حالات لأطفال المصابين بالتوحد المتواجدين بالمراكز النفسية البيداغوجية خاصة، ينتمون إلى أوساط اجتماعية واقتصادية متوسطة ويتمتعون بنفس درجة الإعاقة ولا يعانون من أي اضطرابات أخرى مصاحبة ويتراوح العمر الزمني ما بين (6-8 سنوات). وبتطبيق المنهج المقارن، والبطارية السريعة لتقييم الوظائف المعرفية (BREV) كأداة للدراسة، أسفرت النتائج على أن للإدماج في الأقسام الخاصة لها دور إيجابي في تعزيز الخصائص النمائية للأطفال المصابين بالتوحد، وأنه توجد فروق ذات دلالة إحصائية بين الأطفال المصابين بالتوحد المدمجين بالأقسام الخاصة والأطفال المصابين بالتوحد المتواجدين بالمراكز النفسية البيداغوجية على مستوى كل من الإدراك والذاكرة واللغة. The study aims to identify the impact of the educational program and the integration process in the special departments in developing and enhancing the developmental characteristics of children with autism, Where we chose a sample of 10 children, including five cases of children with autism integrated in special departments and five cases of children with autism who are in private psychological pedagogical centers, they belong to medium social and economic circles and have the same degree of disability and do not suffer from any other accompanying disorders and the chronological age ranges between ( 6-8 years). By applying the comparative method and the rapid battery assessment of cognitive functions (BREV) as a study tool. the results revealed that inclusion in special sections has a positive role in enhancing the developmental characteristics of children with autism, and that there are statistically significant differences between children with autism who are integrated in special departments and children with autism who are in pedagogical psychological centers at the level of Perception, memory and language. .
The role of class special in strengthen the developmental characteristics of in an autistic child - comparative study
مقال
Keywords: التوحد، الأقسام الخاصة، الخصائص النمائية; autism, class special, developmental characteristics.